2019
DOI: 10.1111/aen.12384
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding as a tool for invertebrate community monitoring: a case study comparison with conventional techniques

Abstract: When conserving native biodiversity, it is particularly important to consider invertebrates, a diverse and functionally important component of biodiversity. However, their inclusion in monitoring and conservation planning has lagged behind larger fauna because collecting, sorting and identifying invertebrates using conventional monitoring techniques is often expensive, time consuming and restricted by expertise in diagnostics. Emerging DNA metabarcoding techniques could potentially revolutionise monitoring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 38 publications
(103 reference statements)
2
38
0
Order By: Relevance
“…However, the minimal overlap between our soil and Malaise trap samples may simply reflect that insect communities found in different biological substrates in the same habitat or location differ significantly in composition (Koziol et al, ). For instance, in a study somewhat similar to ours, Watts et al () found big differences in the communities retrieved in soil samples and aboveground traps, although in their case the crawling organisms were retrieved in the aboveground traps, whereas they were primarily found in the soil samples (leaf litter fraction) in our study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, the minimal overlap between our soil and Malaise trap samples may simply reflect that insect communities found in different biological substrates in the same habitat or location differ significantly in composition (Koziol et al, ). For instance, in a study somewhat similar to ours, Watts et al () found big differences in the communities retrieved in soil samples and aboveground traps, although in their case the crawling organisms were retrieved in the aboveground traps, whereas they were primarily found in the soil samples (leaf litter fraction) in our study.…”
Section: Discussionsupporting
confidence: 75%
“…COI primers with lower degeneracy can be useful with eDNA samples, picking up fewer nontarget taxa than degenerate primers while still recovering a good portion of the invertebrate diversity, but they are still likely to result in lower coverage of the target taxon than in bulk samples (e.g. Watts et al, 2019). Our results…”
Section: Malaise Trap Samples Versus Soil Samplesmentioning
confidence: 70%
See 2 more Smart Citations
“…Other novel approaches to monitoring include deploying automated 'biodiversity weather stations' of the type envisaged in Germany to routinely monitor the diversity and abundance of invertebrates (Vogel 2017), the use of higher taxa (e.g. Family-level) as surrogates for species-level identification to monitor changes in invertebrate assemblages (Driessen and Kirkpatrick 2019) and DNA metabarcoding techniques for characterising and monitoring whole invertebrate communities (Watts et al 2019).…”
Section: Temporal Replication Of Surveysmentioning
confidence: 99%